6 RESOLUTION OF PRIAPISM WITH SHUNT PLACEMENT IN SICKLE CELL DISEASE. Issue 1 (1st January 2007) - Atwal, P.; Rehman, M.; Atwal, C.; Niranjan, S.
Abstract : Priapism, an involuntary, persistent erection of the penis, is one of the many serious complications associated with sickle cell disease (SCD). The pathophysiology of priapism involves the failure of detumescence and is the result of underreguluation of arterial inflow or, more commonly, the failure of venous outflow. In SCD, polymerization and sickling of red blood cells lead to the occlusion of the outflow vessels from the corpora cavernosa, resulting in engorgement of the corpora cavernosa. Chronic intravascular hemolysis in SCD is also associated with a state of endothelial dysfunction characterized by reduced nitric oxide, which is a major neurotransmitter controlling erection. There are two types of priapism: stuttering and prolonged (major attack). Stuttering attacks are typically brief (< 3 hours), nocturnal, and recurrent and may predispose to major attacks. Major attacks usually persist for more than 24 hours without detumescence and may lead to irreversible ischemic penile injury, resulting in fibrosis and impotence. A 17-year-old male patient with a history of SCD (HbSS disease) presented with sickle cell crisis manifested by an episode of priapism of more than 20 hours' duration. The patient was started on oxygen, intravenous hydration, and pain medication, without benefit. Intracavernosal aspiration of the corpora cavernosa and intracavernosal instillation of phenylephrine resulted in no improvement. Exchange transfusion with 6 units of packed RBCs led to only minimal relief. Therefore, a Winter shunt was placed by biopsy needle, which resulted in significant detumescence that improved progressively with continued conservative management. Key steps in the management of SCD-associated priapism are oxygenation, analgesics, hydration, alkalization, and exchange transfusion to keep the HbS value less than 30%. Surgical management is generally resorted to when the conservative management fails. However as the time to treatment (resolution of priapism) is the single most important factor affecting outcome in patients with SCD-associated priapism, especially in patients manifesting with prolonged priapism, surgical decompression should be considered as the initial therapy. Prompt treatment may help the patient avoid the medical, social, and psychological implications of this complication of SCD.